Religion and Misconduct Among Prison Inmates in South Korea - Kim, Sohee (International journal of offender therapy and comparative criminology, 2023)
Although faith-based programs are present in most prisons for offender rehabilitation, the effect of religion on prison inmates remains an understudied topic. In addition, existing research shows mixed results about the religious effect. The present study intends to not only advance the understanding of inmate’s prison misconduct but also examine whether religion is likely to contribute to reducing the risk of misconduct using a non-Western sample of inmates. To assess the relationship between inmates’ religion and prison misconduct, we applied negative binomial regression to analyze survey data from 986 Korean adult male inmates. Results showed that inmates who had a religious affiliation with Catholicism or Buddhism were less likely to report prison misconduct than those who had no religion. In addition, the inverse relationship was observed whether inmates had participated in religion before incarceration or came to participate in religion while incarcerated, depending on religious denomination.